2017
DOI: 10.1024/0301-1526/a000600
|View full text |Cite
|
Sign up to set email alerts
|

Long-term individual shear rate therapy counterpulsation enhances plasma nitrite release in patients with PAD

Abstract: We verified that long-term ISRT stimulates the vascular system and exerts a comparable effect to physical exercise in regards to NO release, which coincide with recent findings regarding an improvement of endothelial function. However, further studies are necessary to investigate the role for circulating leukocytes.
.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…According to the studies conducted both on healthy volunteers and on the patients with intermittent claudication, it was found that long-term ISRT led to a significant increase in blood nitrites in the patients with PAD, indicating an increase in NO synthesis and improvement in endothelial function [ 100 ]. In the ISRT study, which included 14 patients with PAD IIb stage according to Fontein, the effect of ISRT on endothelial function and walking distance was studied.…”
Section: Current Therapeutic Approaches Based On the Modulation Of Biomechanical Forcesmentioning
confidence: 99%
“…According to the studies conducted both on healthy volunteers and on the patients with intermittent claudication, it was found that long-term ISRT led to a significant increase in blood nitrites in the patients with PAD, indicating an increase in NO synthesis and improvement in endothelial function [ 100 ]. In the ISRT study, which included 14 patients with PAD IIb stage according to Fontein, the effect of ISRT on endothelial function and walking distance was studied.…”
Section: Current Therapeutic Approaches Based On the Modulation Of Biomechanical Forcesmentioning
confidence: 99%
“…EPT alleviates angina and improves both exercise tolerance and peak oxygen consumption in chronic myocardial ischemia beyond acute hemodynamic effects 2,3 through flow‐mediated NO release, improved endothelial function 4 and positive outward remodeling of collateral arteries. Side effects, however, are plenty, given that conventional high‐pressure EPT machines, called enhanced external counterpulsation (EECP) devices, elicit cuff pressures of 250–300 mmHG.…”
mentioning
confidence: 99%
“…A novel non‐invasive, individualized therapeutic option for arterial dysfunction may hold potential as a therapeutic option for Raynaud's patients: individual shear rate therapy (ISRT), a therapeutic strategy based on low‐pressure external pulsation, that significantly improves clinical outcomes in patients with cardiovascular occlusive disease 16,17 . ISRT increases flow‐induced shear forces on the endothelium rather than increasing blood pressure or cyclic stretch on the vascular wall, 18 thereby inducing flow‐mediated release of NO and improving endothelial function 19 . In primary Raynaud's, the frequently occurring dysregulation of arterial dilatation and vasoconstriction could thus be counteracted by increasing flow velocity, improving endothelial function and increasing NO and shear–stress‐related endothelial function, thus improving arterial blood flow.…”
mentioning
confidence: 99%

Vessels in motion

Persson,
Hillmeister,
Buschmann
et al. 2023
Acta Physiologica
Self Cite